PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
Earnings management is an action manager to manipulate earnings in order to achieve certain goals in earnings reporting. This study aim to determine the effect off size company, profitability, leverage to earnings management on manufacturing companies listed on the Bursa Efek Indonesia period 2014-2016. The simple used in this study is thirty (30) manufacturing companies which is listed on the Bursa Efek Indonesia period 2014-2016. This research use purposive sampling technique with criterion which have been specified. The analysis technique used is multple linear regression analysis. Partial results of the study indicate that the variable size of the company influences earnings management. Profitability variable does not affect earnings management. While the leverage variable does not affect earnings management. The results of the study simultaneously show the influence of firm size, profitability and leverage with earnings management in manufacturing companies listed on the Bursa Efek Indonesia (BEI).